Antibacterial and Antioxidant Characteristics of Zataria multiflora Boiss Essential Oil and Hydroalcoholic Extract of Rhus coriaria L. - A. Mojaddar Langroodi (Journal of Food Quality and Hazards Control, 2019)
Background: The increasing demand for natural preservatives results in their extended usefulness. The objective of the present study was to investigate the physicochemical and antioxidative characteristics of Rhus coriaria L. (sumac) fruit and comparison of its antioxidative and antibacterial activity with Zataria multiflora Essential Oil (ZEO) as native Iranian natural additives. Methods: Antioxidant activities of Z. multiflora Boiss and sumac were analyzed by 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, 2, 2'-azino-bis 3-ethylbenzothiazoline-6-sulphonic acid (ABTS). Reducing power tests were used for measuring antioxidant activity. Total phenolic content of extract and essential oil were studied as well. The Minimal Inhibitory Concentration (MIC), Minimal Bactericidal Concentration (MBC), and Fractional Inhibitory Concentration (FIC) of a hydroalcoholic extract of sumac and ZEO against of Salmonella Typhimurium and Listeria monocytogenes were studied. Statistical analysis of data was performed using the SPSS software. Results: The phenolic content in sumac extract (305.65 mg/g) was significantly (p˂0.05) higher than ZEO (179.42 mg/100 g). The highest level of antibacterial activity was demonstrated by ZEO with the MICs of 0.625 for S. Typhimurium and 1.25 mg/ml for L. monocytogenes. Conclusion: Sumac extract showed more potent antioxidative activity than ZEO. However, based on the results of antibacterial activity, ZEO had more potent than sumac extract, significantly.